The increase of safe abortion compliance - Грищенко, О. В.; Лахно, И. В. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
It was performed the study of impact of the Tranexam on hemostatic indicators and blood loss volume in women those were underwent medical abortion. It was participated 93 patients with early gestation and 30 of whom were practically healthy and made the group I. In group II were 32 pregnant women under observation who have performed abortion in accordance with the Clinical Protocol number 1177. Group III was formed with 31 pregnant ladies whom in addition to the standard protocol of safe abortion have prescribed Tranexam 1 tablet (250 mg) 4 times a day after first taking of mifepristone. Additional intake of Tranexam has allowed supporting the level of platelet aggregation on the background of obvious deficiency of endogenous fibrinolysis inhibitors in the absence of severe hypercoagulation and an increased risk of thrombosis. This helped to reduce the volume and duration of post-abortion bleeding.